Lexicalized Morphosyntactic Transitivity in Urarina (Isolate) - Peña Torrejón, Jaime G. (2025)
This paper examines lexicalized morphosyntactic transitivity in Urarina, a language isolate from Peru, within the typological framework proposed by Payne (2009). It is proposed that transitivity is best seen as a scalar category in different levels of a lexical-clausal organization and that verbal roots of languages like Urarina can be categorized in more specific terms than only a dichotomic transitive/intransitive distinction. Based on their morphosyntactic behavior, we identify at least four types of lexicalized transitivity and six different verb subclasses on account of the typological framework proposed for Urarina. For this purpose, we describe how roots, stems, and affixes involved in increasing or decreasing valence work. It is argued that Urarina presents a very rigorous organization of its transitivity at the lexical level that mostly remains at the clausal level. In this way, this framework has allowed us to show in greater detail the gradual nature of transitivity and its expression across different levels and constructions in the Urarina language.